The Influence of Good Corporate Governance Mechanisms and Corporate Social Responsibility Disclosure on the Financial Performance of LQ45 Companies in Indonesia for the 2022–2024 Period - Putri Ika Safitri; Rusliyawati; Nina Febriana Dosinta (Jurnal Investasi Islam, 2026)
This study aims to analyze the influence of Good Corporate Governance (GCG) mechanisms, proxied by the Board of Commissioners, Board of Directors, and Audit Committee, as well as Corporate Social Responsibility (CSR) disclosure, on the financial performance of LQ45 companies listed on the Indonesia Stock Exchange during the 2022–2024 period in the sustainability reporting era. This study uses a quantitative approach with secondary data obtained from the companies' annual reports and sustainability reports. The research sample consisted of 15 LQ45 companies over three years of observation, resulting in 45 observations. Data analysis was performed using multiple linear regression with the assistance of statistical software. The results show that simultaneously, the Board of Commissioners, Board of Directors, Audit Committee, and CSR significantly influence the company's financial performance. Partially, the Board of Directors and Audit Committee significantly influence financial performance, while the Board of Commissioners and CSR disclosure do not. These findings indicate that the effectiveness of corporate governance is more determined by the decision-making and internal oversight functions carried out by the board of directors and audit committee than by the number of commissioners. Furthermore, CSR disclosure has not been able to have a direct impact on increasing company profitability in the short term. This research provides empirical evidence by presenting the latest evidence on the relationship between GCG mechanisms, CSR, and financial performance in LQ45 companies amidst increasing demands for sustainability reporting. The research findings are expected to serve as a reference for management, investors, and regulators in improving corporate governance and implementing business sustainability.